2022
DOI: 10.1186/s42787-022-00148-9
|View full text |Cite
|
Sign up to set email alerts
|

Poisson–logarithmic half-logistic distribution with inference under a progressive-stress model based on adaptive type-II progressive hybrid censoring

Abstract: The researchers, engineers, and physical experimenters may face difficulty to get a distribution that fits the failure data arising from certain systems. So, in this paper, a new distribution is introduced, named Poisson–logarithmic half-logistic distribution, based on a parallel–series system’s failure times. Specific statistical properties are investigated for the introduced distribution. Also, two real data sets are considered to compare the introduced distribution with some other distributions. The progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…PDF (11) and HRF (12) are plotted in Figure 2 for θ � 1.5, λ � 2.0, and diferent values of c and d. It can be noticed that PDF (11) is always unimodal, while HRF ( 12) is always increasing since β > 2.…”
Section: Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…PDF (11) and HRF (12) are plotted in Figure 2 for θ � 1.5, λ � 2.0, and diferent values of c and d. It can be noticed that PDF (11) is always unimodal, while HRF ( 12) is always increasing since β > 2.…”
Section: Assumptionsmentioning
confidence: 99%
“…Previous studies of the PRSALT have indicated that the imposed stress is expressed as an increasing linear function of time, see [5,6,9]. While in some papers such as [7,11,34], the authors suggested PRSALTs taking into account that the imposed stress is represented as a nonlinear increasing function of time. Te PRSALT is performed under the following fundamental assumptions.…”
Section: Progressive-stress Model Based On the Rayleighmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also be useful in survival analysis and reliability engineering when dealing with skewed data and non-negative lifetimes. Moreover, it has been applied as a life-testing model by several authors, see, for example 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%